Efficacy of topical tacrolimus 0.1% and clobetasol propionate 0.05% in the treatment of alopecia areata - Hossain, Md. Shakhawat; Miah, Md. Titu; Khan, Md. Zulfiqur Hossain; Khondker, Lubna; Hasan, Md. Rashidul (Journal of Pakistan Association of Dermatologists, 2016)
Objective To assess the efficacy of tacrolimus and clobetasol propionate in the treatment of alopecia areata. Methods A clinical trial was carried out in the department of Dermatology and Venereology, Dhaka Medical College Hospital, Dhaka, Bangladesh from May 2013 to April 2014. Total sixty patients were enrolled and divided into group A and group B. Thirty of group A patients were treated with topical tacrolimus and thirty of group B patients were treated with topical clobetasol propionate. Results In group A, the duration of illness ranged from 2 months to 36 months and in group B, from 1 month to 24 months. Among the patients of group A and B, 25 (83.3%) and 27 (90%) patients improved, respectively. After 16th week of treatment, slight response in 6 (20%) and 4 (13.3%) and moderate response in 18 (59.4%) and 22 (63.2%) and marked response in 1 (3.3%) and 1 (3.3%) was seen in group A and group B, respectively. No significant difference was observed (p value = 0.648). Conclusion Both the drugs, clobetasol propionate and tacrolimus when used individually, were found to be equally effective in the treatment of alopecia areata and tacrolimus ointment 0.1% can be used as an alternate therapeutic modality.